Heterotopias da festa:os muitos carnavais de Caetano Veloso - Kleaim, Luiz Cláudio (2011)
This work of literacy criticism and literature is based on analysis of the weaving songs in the book Muitos Carnavais by Caetano Veloso, taking as its starting point the theme of love (romantic love X passion play) in the space of carnival, intersecting studies of historiography and sociology, questioning the nuances of political space, and its artistic and social developments, such as political, and artistic creation “selfrealization” of (and respect for) gay subjectivities. It is a singer who was one of the creators of the artistic movement known as Tropicalism, mobilizing our society in many ways and that decisively influenced the artistic creation and behavior, the proposal was not enough to have the Tropicalia movement akin to the language carnival. To this end, we seek to analyze the corpus privileged above understanding it through the historical background, social and political movement that erupted Tropicalism, and punctuate it by the way in which links to the influences of the Manifest Anthropophagic by Oswald de Andrade, and with the history and language carnival. In addition, strives through historiography and political sociology observe a synthetic approach of prevailing views about the carnival, adding these perspectives to possible readings that can make use of space carnival, including the system of power that favors (provide) social prestige to certain sexual identities, analyzing the insertion within the carnival in recent years the figure of the homosexual, its appropriations and achievements: a rapprochement between the myth and the lived, the utopian space and other (heterotópico) in the hope to contribute to systematize thoughts involving concepts such as culture and popular music, artistic and musical movement, sexuality, love and power.